A influência do período de internação no declínio da capacidade funcional do paciente idoso: revisão sistemática - Paiva, Lidiane R. F. de Oliveira de (2022)
Population aging is a phenomenon that has become the subject of several discussions nowadays, because during this process there may be a decline in the Functional Capacity (FC) of the elderly, especially during hospitalization, resulting in loss of muscle mass and strength (sarcopenia). , malnutrition and other diseases so common in old age. This decrease in FC generates a greater dependence of the elderly, possible readmissions and a decrease in Quality of Life (QoL), hence the importance of its evaluation. Therefore, this systematic review aimed to investigate the influence of the hospitalization period on the decline in the functional capacity of the elderly. The PRISMA method and RAYYAN software were used in this review, conducted according to the guidelines of the Cochrane Handbook for Systematic Reviews of Interventions, the PECO strategy was necessary for the construction of the research question. A search was carried out in the following databases: Medline/Pubmed, The Cochrane Library, Scielo, CINAHL, Google Scholar and BVS, until March 2022, using MeSH terms and Boolean operators, the selected search strategy and methods were registered in the database of PROSPERO data (#CRD42022316496). Considering the inclusion and exclusion criteria, there were twenty-seven studies that investigated 13,039 hospitalized elderly. After analysis, it was found that hospitalization directly influences the Decline in Functional Capacity, especially when it comes to elderly patients, and the longer the period in which they remain hospitalized, the more pronounced this decline will be.